The High School Student’s Perception of Sexual Behavior - Winda Oktaviani; Khairani Khairani (Jurnal Neo Konseling, 2021)
In adolescence, not only physical changes occur but also changes in sexual attitudes and behavior. During its development, adolescents already know the opposite sex and like the opposite sex. This means that interest in sex in adolescents increases. However, sexual behavior in adolescents is increasingly worrying, there has been a change in sexual outlook and behavior in society. Sexual behavior such as holding hands, which is a common practice of hugging while driving, is often seen in general. This study aims to describe students' perceptions of sexual behavior in various forms. This research uses quantitative methods with a descriptive approach. The population of this study were students of class X and XI SMA Kartika 1-5 Padang, totaling 412 people. The sampling technique was carried out using simple random sampling technique. The research sample amounted to 205 people. The research was carried out by administering the Likert scale model research instrument. Data were analyzed using percentage techniques. The findings of this study indicate that students' perceptions of sexual behavior are in the medium category with a percentage (37.6%) in terms of: (1) biological aspects are in the Very High category with a percentage (37.6%), (2) psychological aspects are in the Very High category with a percentage (34.6%), (3) the social aspects are in the Very High category with a percentage (50.2%), (4) the moral aspects are in the Very High category with a percentage (47.8% ). Based on the results of this study, it is hoped that the Guidance and Counseling Teacher at School, in order to correct the wrong perceptions of students regarding perceptions of sexual behavior.